Fighting against Climate Change: a Non- Traditional Security Threat and Adaptation Challenges in Bangladesh - Kutub Uddin Ahmad; Md Amirul Islam (International Journal of Applied Research and Sustainable Sciences, 2023)
For instance, climate change has become an overwhelming concern worldwide. One million deaths occur annually due to problems with climate change, making it the most dangerous nation in Asia, which makes this matter an international concern. This study examines the impact of climate change on immigration, food security, and healthcare. The governmental efforts towards countering climate change in Bangladesh: research Therefore, this report is able to contribute to the campaigns of Bangladesh in international forums against climate change. Climate change affects every country on Earth, and Bangladesh is struggling with it. This is due to the politics involved in the global climate negotiations as well as the extensive investment needed to push onward. Lastly, this study provides several solutions on how they can solve this big hazard in Bangladesh and around the world. Lastly, this study provides several solutions to solve this important risk for Bangladesh as well as the world at large.